O equilíbrio e o medo de sofrer quedas em pacientes portadores da doença pulmonar obstrutiva crônica - Pedrozo, Michelle Difante (2012)
Body balance is one of the most important functions of the organism and it is associated with the individual s quality of life. So, the chronic obstructive pulmonary disease (COPD) causes pulmorary alterations, and it also causes several systemic involvements, which are mainly related to physical deconditioning, muscular weakness, which probably influence balance. Thus, it is extremely important to make a sensible investigation of the implications of this disease, related to functional stability. Therefore, this study had the purpose to evaluate the body balance and fear of falling of people who have COPD and to establish the comparison with subjects, into the same age group, who do not have COPD. The study group consisted of 29 subjects with the disease who had age average of 64.72 ± 7.67. The 24 subjects of the control group had age average of 63.58 ± 8.17. To evaluate the balance and motor function, the patients were submitted to Dynamic Posturography Foam-laser (FLP), Timed Up and Go Test (TUG) and the Berg Balance Scale (BBS); and to evaluate the functional limitation which results from patient s dyspnea, the Research Council (MRC) scale was used. The fear of falling was also investigated through the Falls Efficacy Scale - International Among Elderly Brazilians (FES-I-BRAZIL). The data were statistically analyzed through the program Statistical Analysis System (SAS) 9.2. The test Mann-Whitney was used to compare the groups, and the significance level considered was 0.05. It was observed by the FLP, that there were no significant differences between the groups, independent of the disease progression. However, when compared the results of TUG and BBS, there was significant difference between the groups, the sick subjects had worse performance. The same group presented worse scores related to fear of falling, when evaluated through FES-I-BRAZIL. After this study, it is possible to conclude that individuals with COPD presented body balance alterations and higher fear of falling occurrence.